A neuropathological study of novel RTTN gene mutations causing a familial microcephaly with simplified gyral pattern. Issue 7 (22nd January 2018) - Chartier, Suzanne; Alby, Caroline; Boutaud, Lucile; Thomas, Sophie; Elkhartoufi, Nadia; Martinovic, Jelena; Kaplan, Josseline; Benachi, Alexandra; Lacombe, Didier; Sonigo, Pascale; Drunat, Séverine; Vekemans, Michel; et al.
Abstract : Background: The RTTN gene encodes Rotatin, a large centrosomal protein involved in ciliary functions. RTTN mutations have been reported in seven families and are associated with two phenotypes: polymicrogyria associated with seizures and primary microcephaly associated with primordial dwarfism. Case: A targeted exome sequencing of morbid genes causing cerebral malformations identified novel RTTN compound heterozygous mutations in a family where three pregnancies were terminated because a severe fetal microcephaly was diagnosed. An autopsy performed on the second sib showed moderate growth restriction and a microcephaly with simplified gyral pattern. The histopathological study discovered a malformed cortical plate. Conclusions: The present study confirms the involvement of RTTN gene mutations in microcephaly with simplified gyral pattern and describes the observed abnormal neuropathological findings.